Hepatitis C virus clearance by direct‐acting antiviral treatments and impact on insulin resistance in chronic hepatitis C patients. Issue 7 (27th February 2018) - Adinolfi, Luigi E; Nevola, Riccardo; Guerrera, Barbara; D'Alterio, Giovanni; Marrone, Aldo; Giordano, Mauro; Rinaldi, Luca
Abstract: Background and Aim: Chronic hepatitis C virus (HCV), particularly genotype 1, is associated with insulin resistance (IR) and diabetes. This study evaluated the impact of HCV clearance by all‐oral direct‐acting antiviral treatments on IR and glycemic control. Methods: Included in this prospective case–control study were 133 consecutive HCV‐genotype 1 patients with advance liver fibrosis (F3–F4) without type 2 diabetes. Sixty eight were treated with direct‐acting antiviral and 65 were untreated. Liver fibrosis was assessed by transient elastography. Pre‐treatment, end‐treatment, and 3 months post‐treatment withdrawal IR homeostasis was assessed by homeostatic model assessment (HOMA)‐IR, HOMA‐S, and HOMA‐B . Results: At baseline, treated, and untreated patients showed similar liver fibrosis levels, HOMA‐IR was 4.90 ± 4.62 and 4.64 ± 5.62, respectively. HOMA‐IR correlated with HCV RNA levels. At the end of treatment, all patients cleared HCV RNA, regardless of liver fibrosis and body mass index, and a reduction in HOMA‐IR at 2.42 ± 1.85 was showed ( P < 0.001); in addition, increased insulin sensitivity, decreased insulin secretion, reduction of serum glucose, and insulin levels were observed. Data were confirmed 3 months after treatment withdrawal in the 65 patients who cleared HCV. No variation occurred in untreated patients. Overall, 76.5% of sustained virologic response patients showed IR improvements, of which 41.2% normalized IR. Improvement of IR was strictly associated with HCV clearance; however, patients with the highest levels of fibrosis remain associated with some degree of IR. Conclusions: The data underline a role of HCV in development of IR and that viral eradication reverses IR and improves glycemic control and this could prevent IR‐related clinical manifestations and complications.